Visionary: A Tool for Managing Institutional Objectives - Másquez Monteza, Sócrates; Gamboa Ahuite, Richard; Quinto Huamán, Carlos; Johnson Tuanama, Martin; Ochoa Castillo, Percy Fortunato (LACCEI, 2025)
The Institutional Strategic Plan (PEI) is an essential tool for the planning and management of objectives at the state level, aimed at improving the efficiency of public institutions. In this context, the Peruvian Army faces significant challenges in managing its strategic goals, which has driven the development of specialized software to optimize this process. Visionary is a solution designed to manage physical and financial goals, while also facilitating interdepartmental communication and optimizing decision-making. The system offers multiple benefits, such as the automatic generation of reports, a chat feature with artificial intelligence functions, and an interactive dashboard that allows real-time visualization of objective progress. The proposal incorporates surveys based on the Likert scale, targeted at high-ranking officials and administrative personnel, to evaluate the software’s effectiveness. Its implementation at the Scientific and Technological Institute of the Army (ICTE) has demonstrated that Visionary is a modular and scalable system. The results showed that the tool enhances resource optimization and operational execution, significantly contributing to the achievement of strategic objectives. However, areas such as logistics were identified as having a lower impact, suggesting the need for specific adjustments to boost its effectiveness across all sectors.